Salvage Total Laryngectomy Swallowing Outcomes Based on Flap Reconstruction: Onlay vs Incorporated Technique. (December 2021) - Ziegler, Andrea; Pittman, Amy; Thorpe, Eric
After a salvage total laryngectomy, one of patients' primary goals is to resume oral intake. This retrospective chart review included all patients who underwent a salvage total laryngectomy with free or pedicled flap reconstruction to compare swallowing outcomes in those with an incorporated flap or primary pharyngeal closure with an onlay flap. There was no significant difference in the ability to achieve complete feeding tube independence or the time that it took to achieve independence. Patients with an onlay flap had significantly lower rates of subjective dysphagia and stricture as compared with patients with incorporated flaps. Incorporated fasciocutaneous flaps showed no significant difference from onlay flaps in terms of outcomes. However, incorporated musculocutaneous flaps showed higher rates of subjective dysphagia and stricture when compared with onlay flaps. Patients undergoing a salvage total laryngectomy and reconstruction with an onlay flap had significantly less postoperative dysphagia and stricture than patients with a musculocutaneous incorporated flap.